Private London - Patterson, James, 1947- (Patterson, James, 1947- Private novels., 2012)
Terror has followed beautiful young American Hannah Shapiro to London, and now it is down to former Royal Military Police Sergeant Dan Carter, head of Private London, to save her all over again. In central London, young women are being abducted off the street. When the bodies are found, some days later, they have been mutilated in a particularly mysterious way.